Digital angioplasty ballon inflation device for interventional cardiovascular procedures - Fan, Zhong (2008)
Percutaneous Transluminal Coronary Angioplasty (PTCA) is an important interventional procedure performed everyday in major hospitals. In this dissertation, we describe our new designed device for angioplasty catheter ballon inflation. It is a digital system that can be used in the actual PTCA procedure.